Sustainability of Blue Economy Resource as Economic Recovery Sukolilo MSMe Group - Muliatie, Yurilla Endah; Suwondo, Ampar Jaya; Sujani, Sujani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
This community service was conducted at the MSME partner group Toko Krupuk Risma in Sukolilo, Surabaya. The problems of service partners are that Product quality could be more consistent, Adequate packaging binders are needed for the packaging process of goods, The use of payment transactions is still manual, and Financial policy still needs to be improved. The objectives of this study were to improve product consistency, provide training on the use of strapping equipment, provide training and assistance in payment transaction automation literacy, and provide training and assistance in financial policymaking. The stages of implementing this community service include Preparation, Implementation, Internal Monev, Program Evaluation, and Program Sustainability. The approach methods used in this community service are Training and Discussion. As a result of community service, there was an increase in product consistency with the spice grinder provided. There is an improvement in the quality of product packaging, and virtual transaction payments are well implemented. In addition, decision-making policies are based on good data processing after an increase in partner literacy by the implementation team. The implementation team assisted in establishing a monitoring and evaluation system to track the impact of implementing blue economy principles in Krupuk Risma's business. The implementation team continues to guide store owners and employees in adopting blue economy principles in partners' day-to-day operations.